MICROSCOPIA ELETRÔNICA DE VARREDURA COM TARDÍGRADOS (FILO TARDIGRADA): SUGESTÃO DE PROTOCOLOS ADAPTADOS ÀS PECULIARIDADES DO GRUPO - Jr, Edivaldo L. Gomes; Rocha, Clélia M. C. da (Revista Nordestina de Zoologia, 2015)
Existing protocols for processing biological samples for scanning electron microscopy (SEM) usually do not produce good results when applied to tardigrades. This study aimed to test standard protocols for invertebrates in order to obtain better results with samples from this group. The two suggested protocols describe the preparation steps of the material, such as clamping, form of packaging of the specimens, rinses, post-fixation, dehydration, critical point drying and the manner of use of the SEM. In the "Protocol suggestion A" the material is fixed in 4% formaldehyde, rinses with sodium cacodilato buffer and distilled water, post-fixation with osmium tetroxide, dehydration with acetone, drying the sample to critical point with CO2, metallization in gold and the microscope configured in high vacuum mode. In the "Protocol suggestion B" the material is fixed in 70% ethanol, the samples are enclosed in capsules closed by meshes without washing steps and post-fixation. Dehydration is performed in ethanol and acetone, critical point drying with CO2, metallization in gold and the microscope configured to high vacuum mode.